Knowledge and Awareness Regarding Radiation Safety among Radiology Study Program Students - Felayani, Fadli; Wibowo, Ardi Soesilo; Amin, Kholik Al (Sean Institute, 2023)
The increasing use of radiation in health services increases the risk to the public. The radiology study program as a producing institution has the challenge of ensuring that students fully understand and are aware of radiation safety. This study aims to determine the level of knowledge and awareness regarding radiation safety and related factors among radiology study program students.This was a quantitative study with a survey approach. The study instrument was a questionnaire that was delivered to 140 students from 7 radiology study programs in Indonesia consisting of 2 state institutions and 5 private institutions. The questionnaire consisted of 12 questions to evaluate knowledge regarding radiation safety, 16 questions to evaluate awareness regarding radiation safety and 6 questions to evaluate the learning experiences.Based on the study results on knowledge regarding radiation safety, 12.86% of respondents had